Influence of fire retardants on the reaction‐to‐fire properties of coextruded wood–polypropylene composites. (19th March 2015) - Nikolaeva, Marina; Kärki, Timo
Summary: The reaction‐to‐fire properties of coextruded wood–plastic composites containing different fire retardants (melamine, zinc borate, ammonium polyphosphate, aluminium trihydroxide, natural flake graphite and expandable graphite) in the shell layer have been studied with the cone calorimetry technique. The effect of ammonium polyphosphate in combination with graphite has also been studied with a cone calorimeter test. A coextruded composite manufactured without any fire retardant addition has been used as a reference. The fire properties measured in the cone calorimeter are discussed, including the heat release rate, total heat release, smoke production, specific extinction area, CO yield and mass loss rate. The results show that the introduction of fire retardants in the shell layer of coextruded wood–polypropylene composites has a favourable effect on the fire resistance properties of the composite materials. The reaction‐to‐fire properties have been improved according to the fire classification of construction products based on the Euroclass system. Copyright © 2015 John Wiley & Sons, Ltd.